Animal Violence Demystified - Natarajan, Deepa (Frontiers Research Foundation, 2010)
Violence has been observed in humans and animals alike, indicating its evolutionary/biological significance. However, violence in animals has often been confounded with functional forms of aggressive behavior. Currently, violence in animals is identified primarily as either a quantitative behavior (an escalated, pathological and abnormal form of aggression characterized primarily by short attack latencies, and prolonged and frequent harm-oriented conflict behaviors) or a qualitative one (characterized by attack bites aimed at vulnerable parts of the opponent's body and context independent attacks regardless of the environment or the sex and type of the opponent). Identification of an operational definition for violence thus not only helps in understanding its potential differences from adaptive forms of aggression but also in the selection of appropriate animal models for both. We address this issue theoretically by drawing parallels from research on aggression and appeasement in humans and other animals. We also provide empirical evidences for violence in mice selected for high aggression by comparing our findings with other currently available potentially violent rodent models. The following violence-specific features namely (1) Display of low levels of pre-escalatory/ritualistic behaviors. (2) Immediate and escalated offense durations with low withdrawal rates despite the opponent's submissive supine and crouching/defeat postures. (3) Context independent indiscriminate attacks aimed at familiar/unfamiliar females, anaesthetized males and opponents and in neutral environments. (4) Orientation of attack-bites toward vulnerable body parts of the opponent resulting in severe wounding. (5) Low prefrontal serotonin (5-HT) levels upon repeated aggression. (6) Low basal heart rates and hyporesponsive hypothalamus–pituitary–adrenocortical (HPA) axis were identified uniquely in the short attack latency (SAL) mice suggesting a qualitative difference between violence and adaptive aggression in animals.